Construction of PANI/Sb2S3 p-n Junction Photoanode for Enhancing Photoelectrochemical Water Oxidation. Issue 6 (8th June 2021) - Liang, Yanqing; Wang, Jun; Liu, Fangyang; Jia, Ming; Jiang, Liangxing
Abstract : Antimony sulfide (Sb2 S3 ) is an emerging photovoltaic material that comprises earth-abundant, non-toxic constituents and has a high absorption coefficient (>10 4 cm −1 ). Nevertheless, the serious bulk recombination phenomenon and the slow electrochemical reaction kinetics on the surface of Sb2 S3 electrode restrict its application in the photoelectrochemical (PEC) water splitting. Herein, we have designed a polyaniline (PANI)/Sb2 S3 p-n junction photoanode successfully to address these issues. With the modification of in-situ anchored PANI, the composite electrode exhibits enhanced light-absorption and accelerated charge transfer efficiency. As a result, the photocurrent density of optimized PANI/Sb2 S3 photoanode is about twice of pristine Sb2 S3, being a promising material for PEC water splitting.